Did COVID-19 Affect the Division of Labor within the Household? Evidence from Two Waves of the Pandemic in Italy - Daniela Del Boca; Noemi Oggero; Paola Profeta; Maria Cristina Rossi (Institute of Labor Economics (IZA), 2021)
The COVID-19 pandemic has had a dramatic impact on families' lives, with parents all over the world struggling to meet the increased demands of housework, childcare and home-schooling. Much of the additional burden has been shouldered by women, particularly in countries with a traditionally uneven division of household labor. Yet the dramatic increase in remote work from home since the pandemic also has the potential to increase paternal involvement in family life and thus to redress persistent domestic gender role inequalities. This effect depends on the working arrangements of each partner, whether working remotely, working at their usual workplace or ceasing work altogether. We examine the role of working arrangements during the pandemic on the traditional division of household labor in Italy using survey data from interviews with a representative sample of working women conducted during the two waves of COVID-19 (April and November 2020). Our data show that the gender gap in household care related activities was widest during the first wave of the pandemic, and although it was less pronounced during the second wave, it was still higher than pre-COVID-19. The time spent by women on housework, childcare, and assisting their children with distance learning did not depend on their partners' working arrangements. Conversely, men spent fewer hours helping with the housework and distance learning when their partners were at home. It is interesting, however, that although men who worked remotely or not at all did devote more time to domestic chores and child care, the increased time they spent at home did not seem to lead to a reallocation of couples' roles in housework and child care. Finally, we find that working arrangements are linked to women's feelings of uncertainty, with heterogeneous effects by level of education.
Keywords: J13; J16; J21; 330; COVID-19; work arrangements; housework; childcare; distance learning